2016
DOI: 10.1007/s12275-016-6312-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of norovirus in asymptomatic food handlers in Busan, Korea, and emergence of genotype GII.17

Abstract: The molecular epidemiology of norovirus infections was studied in food handlers without any symptoms from January to December 2015 in Busan city, Korea. A total of 2,174 fecal specimens from asymptomatic food handlers were analyzed, and 2.3% (49/2,174) were norovirus-positive. Fourteen of 335 samples (4.2%) were positive in January; fifteen of 299 samples (5.0%) in February, and seven of 189 samples (3.7%) in December. However, norovirus was rarely detected in other months. From sequencing analysis, 11 genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
1
12
1
Order By: Relevance
“…In the only previous study of NoV infections in Indonesia, NoV was not found in the control subjects (Subekti et al, 2002b). The prevalence of asymptomatic NoV infection in our present investigation was higher than those reported in non-outbreak settings: 11.9% of a series of food handlers in Japan (Okabayashi et al, 2008), and 1.02%−2.3% in food handlers in Korea (Jeong et al, 2013;Koo et al, 2016) had asymptomatic NoV infection. However, a study performed in a small community in southwestern Cameroon found high asymptomatic NoV prevalences of 27% in adults and 30.8% in children (Ayukekbong et al, 2014a).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In the only previous study of NoV infections in Indonesia, NoV was not found in the control subjects (Subekti et al, 2002b). The prevalence of asymptomatic NoV infection in our present investigation was higher than those reported in non-outbreak settings: 11.9% of a series of food handlers in Japan (Okabayashi et al, 2008), and 1.02%−2.3% in food handlers in Korea (Jeong et al, 2013;Koo et al, 2016) had asymptomatic NoV infection. However, a study performed in a small community in southwestern Cameroon found high asymptomatic NoV prevalences of 27% in adults and 30.8% in children (Ayukekbong et al, 2014a).…”
Section: Discussioncontrasting
confidence: 80%
“…Kawasaki, which is prevalent in East Asian countries such as Japan, China and Korea (Koo et al, 2016;Wang et al, 2016), GII.4 Sydney 2012, which has been the most prevalent in worldwide outbreaks (Eden et al, 2014), and GII.1, which was found to be prevalent in Hawaii and the United Kingdom (Bon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…During the period from January to December 2014, a total of 184 out of 4549 stool samples were identified and positively screened for norovirus; the total asymptomatic infection rate was 4.04% among all age groups. The highest infection rate was detected in January (7.72%), July (8.52%) and December (9.82%); these results very similar with data from Netherlands (5.2%) [6], somewhat higher compared with data from Korea (2.3%) [13] and significantly lower compared with data from Japan (12%) [14] and England (12%) [4]. The study carried out in Netherlands was based on community population; studies in Korea and Japan were based on food handlers, while the study in England investigated all age groups between 1993 and 1996.…”
Section: Discussionsupporting
confidence: 84%
“…The current Food Safety Act does not provide the necessary criteria for patients during shedding. Under these hazardous circumstances, several recent cross-sectional studies on norovirus in Korea [43,66] have revealed the state of the asymptomatic carriers by analyzing stool samples of the food handlers. The samples were collected for legal monitoring of S. typhi at the local health centers.…”
Section: Epidemiological Methodologymentioning
confidence: 99%
“…The most adopted type of study is the retrospective cohort study that establishes exposure and non-exposure groups, while backtracking the time (Tables 1 and 2). Owing to the cost and time effectiveness of cross-sectional studies, surveillance aimed at asymptomatic patients has been conducted [22,43,66]. In contrast, only a few cohort studies have been conducted in Korea compared with foreign nations, most probably because of their shortcomings, such as increased cost and/or duration [44].…”
Section: Epidemiological Methodologymentioning
confidence: 99%